Research on International Police Cooperation from the Perspective of Foreign - Related Rule of Law - Taking Lancang - Mekong Law Enforcement and security Cooperation as an Example - Zheng, Zhichao; Ma, Shuqi (Journal of Theory and Practice of Social Science, 2024)
The current level and capacity of China's international police cooperation is clearly unable to adapt to the evolving and increasingly rampant situation of transnational crime. In order to better safeguard national interests, it is necessary to strengthen the guidance of foreign-related rule of law thinking on international police work. As a good example of international police cooperation, the Lancang Law Enforcement and Security Cooperation (LLEC) is a good example of international police cooperation, which is a good example to think about the internal logic between international police cooperation and the rule of law, analyse the shortcomings and deficiencies in legislation, treaties, jurisdiction, platforms and talents, and then put forward a path to optimize the international police cooperation under the perspective of the rule of law and propose policies and recommendations for the deepening of China's international police cooperation in the Lancang Basin. Suggestions.